Improvement Review of Road Network Connectivity (Case Study: Transport Infrastructure Lueng Daneun - Awe Geutah) - Suriadi; A. Napangala; Radiansyah; Sahrial; Beni Asri; N. Usrina (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
Infrastructure development is one of the sectors currently being pursued by the government to support the standard of living of the people, in order to lead to the era of globalization. In this context, various regions have been marked by the development of the residential sub-sector which aims to support smooth transportation, the economy from one region to another. To anticipate traffic flow on the Leung Daneun-Awe Geutah road, Peusangan Siblah Krueng District, Bireuen Regency. One way is to overlay or add thickness and smoothen the existing road surface, so that with this effort it can smoothen traffic density in Peusangan Siblah Krueng District with a length of STA 0+000 to STA 5+000 where the road length is 5 km with a road width of 9 meters, with work scheduling management for 34 days while the consultant's planning time is 58 days, the difference obtained is 24 days, thus the author's scheduling results are more effective than the consultant's planning time. In implementing this road project, it is necessary to have a method of dealing with and preventing problems in the field. In order to prevent various problems in the field, it is necessary to create a resource utilization program that includes programs for employee, equipment, materials, work methods and implementation.